PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PABRIK GULA REJO AGUNG MADIUN - Yusuf Agung Trilaksono (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine how the compensation provided in PG Rejo Agung Madiun, want to know the performance of employees at PG Rejo Agung Baru Madiun and to determine the effect of compensation on employee performance in PG Rejo Agung Madiun.The sampling technique in this study is simple random sampling. The population in this study are all permanent employees of the PG Rejo Agung Baru Madiun numbering 104 people, while being taken as a sample of 50 people. For data analysis used a linear regression analysis, t-test, correlation and independent sample t test.The results showed that the regression Y = 43.534 + 0,276X, constants of 43.534, meaning if there is no variable compensation (X), then the employee's performance of 43.534 units and the coefficient of the variable compensation (X) of 0.276 means that if the variable compensation (X) increased by one unit, the performance of employees will increase by 0,276 units. Furthermore, from the results of independent t test results obtained -thitung< -ttabel (-2.247 <-1.9845) or Sighit< Sigprob (0.027 <0.05), meaning that compensation has different influence on the performance of employees in PG Rejo Agung Madiun.